2020
DOI: 10.1155/2020/6096280
|View full text |Cite
|
Sign up to set email alerts
|

Modern Family Planning Utilization and Its Associated Factors among Currently Married Women in Rural Eastern Ethiopia: A Community-Based Study

Abstract: Background. The use of modern family planning methods among women of reproductive age (15-49 years) is of public health importance in Ethiopia. Nationally, modern family planning method use remains as low as 35%. Understanding factors associated with the use of modern family planning methods may help to improve maternal and child health. Hence, this study is aimed at assessing modern family planning method use and its determinants among women of reproductive age in the rural districts of Eastern Hararghe zone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
4
6
2
Order By: Relevance
“…As increased in the number of known modern contraceptive methods, modern contraceptive utilization also increased. The same finding can be seen in the Senegal study [ 38 ], Ethiopia study [ 39 ], and Nigeria study [ 40 ]. It might be due to youth with high knowledge of contraception having a better choice of modern contraception and more likely to have a positive attitude towards using modern contraception [ 37 ].…”
Section: Discussionsupporting
confidence: 83%
“…As increased in the number of known modern contraceptive methods, modern contraceptive utilization also increased. The same finding can be seen in the Senegal study [ 38 ], Ethiopia study [ 39 ], and Nigeria study [ 40 ]. It might be due to youth with high knowledge of contraception having a better choice of modern contraception and more likely to have a positive attitude towards using modern contraception [ 37 ].…”
Section: Discussionsupporting
confidence: 83%
“…This rapid decline in OCP may potentially indicate the possible discontinuity of FP workers’ visit, the periodicity of renewal, the susceptibility to stock-outs, and global supply chains disruptions amid COVID-19 pandemic [ 18 ]. Inconsistent with earlier studies, this study found that women who ever used OCP were less likely to use FP compared to women who never used OCP [ 41 ]. This can be because previous users of OCP were more familiar with its detrimental effects.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, the study shows that having adequate knowledge on contraceptive methods motivated the utilization by almost two-folds compared to those who were not. This fact was supported by a study on married women on contraceptive utilization, where the odds of utilization increased by 16-folds [35]. In addition, the ndings are in line with [36] who found that adequate FP knowledge increased the utilization.…”
Section: Discussionsupporting
confidence: 83%